Nedd4-2 haploinsufficiency causes hyperactivity and increased sensitivity to inflammatory stimuli - Yanpallewar, Sudhirkumar (Sci Rep, 2016)
Nedd4-2 (NEDD4L in humans) is a ubiquitin protein ligase best known for its role in regulating ion channel internalization and turnover. Nedd4-2 deletion in mice causes perinatal lethality associated with increased epithelial sodium channel (ENaC) expression in lung and kidney. Abundant data suggest that Nedd4-2 plays a role in neuronal functions and may be linked to epilepsy and dyslexia in humans. We used a mouse model of Nedd4-2 haploinsufficiency to investigate whether an alteration in Nedd4-2 levels of expression affects general nervous system functions. We found that Nedd4-2 heterozygous mice are hyperactive, have increased basal synaptic transmission and have enhanced sensitivity to inflammatory pain. Thus, Nedd4-2 heterozygous mice provide a new genetic model to study inflammatory pain. These data also suggest that in human, SNPs affecting NEDD4L levels may be involved in the development of neuropsychological deficits and peripheral neuropathies and may help unveil the genetic basis of comorbidities.